2019
DOI: 10.1111/sms.13394
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal excitability can discriminate quadriceps strength indicative of knee function after ACL‐reconstruction

Abstract: Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements) that might pose a conflict of interest in connection with the submitted article.Purpose: To investigate relationships between quadriceps strength and neural activity, and to establish a clinical threshold of corticospinal excitability able to discriminate between patients with quadriceps strength indicative of satisfactory and unsatisfactory knee function afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…A number of studies now indicate that corticospinal excitability alterations exist in patients that have returned to sport post ACLR and these alterations are related to quadriceps strength. [9][10][11][12][13][14]17 Therefore in human and animal models. [31][32][33][34] In conclusion, athletes after ACLR demonstrated interlimb differences in ICF during the course of post-operative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies now indicate that corticospinal excitability alterations exist in patients that have returned to sport post ACLR and these alterations are related to quadriceps strength. [9][10][11][12][13][14]17 Therefore in human and animal models. [31][32][33][34] In conclusion, athletes after ACLR demonstrated interlimb differences in ICF during the course of post-operative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, no studies to date have examined the relationship between intracortical excitability and quadriceps strength. However, studies have found that less corticospinal excitability (ie, higher motor thresholds) is associated with poorer quadriceps strength in patients after ACLR 10,17 . Understanding how the balance between inhibitory and facilitatory networks change in response to rehabilitation, and the relationship between these networks and quadriceps strength is needed to improve post‐operative rehabilitation protocols and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased cortical excitability means that knee-injured patients need more stimulation to yield sufficient excitation in the primary motor cortex to generate muscle activation [ 98 ]. While the clinical importance of these changes in corticospinal and spinal-reflexive pathways is not fully understood, recently it has been shown that corticospinal adaptations are correlated with muscle strength and patient-reported knee function satisfaction following ACLR [ 99 ]. It may be that the decrease in cortical excitability is a protective long-term motor cortex adaptation, while a compensatory reflex mechanism maintains required muscle function when needed i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lower quadriceps strength have been shown to demonstrate neural adaptations after ACLR. 5,28 It is unknown if these underlying neurophysiologic adaptations influence the ability to regain muscle strength during the time of return to sport after ACLR. A duration of 2 months between visits was able to acceptably discriminate patients who were able to increase their knee extensor LSI by !5.75%.…”
Section: Discussionmentioning
confidence: 99%